Social Determinants of Health Including Child Opportunity Index Leading to Gaps in Care for Patients With Significant Congenital Heart Disease - Abbas H. Zaidi; Susan F. Saleeb; Michelle Gurvitz; Emily Bucholz; Kimberlee Gauvreau; Kathy J. Jenkins; Sarah D. de Ferranti (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Gaps in care (GIC) are common for patients with congenital heart disease (CHD) and can lead to worsening clinical status, unplanned hospitalization, and mortality. Understanding of how social determinants of health (SDOH) contribute to GIC in CHD is incomplete. We hypothesize that SDOH, including Child Opportunity Index (COI), are associated with GIC in patients with significant CHD. Methods and Results A total of 8554 patients followed at a regional specialty pediatric hospital with moderate to severe CHD seen in cardiology clinic between January 2013 and December 2015 were retrospectively reviewed. SDOH factors including race, ethnicity, language, and COI calculated based on home address and zip code were analyzed. GIC of >3.25 years were identified in 32% (2709) of patients. GIC were associated with ages 14 to 29 years (P<0.001), Black race or Hispanic ethnicity (P<0.001), living ≥150 miles from the hospital (P=0.017), public health insurance (P<0.001), a maternal education level of high school or less (P<0.001), and a low COI (P<0.001). Multivariable analysis showed that GIC were associated with age ≥14 years, Black race or Hispanic ethnicity, documenting <3 caregivers as contacts, mother's education level being high school or less, a very low/low COI, and insurance status (C statistic 0.66). Conclusions One‐third of patients followed in a regional referral center with significant CHD experienced a substantial GIC (>3.25 years). Several SDOH, including a low COI, were associated with GIC. Hospitals should adopt formal GIC improvement programs focusing on SDOH to improve continuity of care and ultimately overall outcomes for patients with CHD.